S01-5: Integrating Physical Activity for Global, Public, and Individual Health Outcomes (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This Joint Statement proposes a coordinated, forward-looking strategy to address the global crisis of physical inactivity (PI), which signiﬁcantly contributes to noncommunicable diseases (NCDs), mental health challenges, and health inequities across the lifespan. It presents a roadmap for a more active, healthier, and sustainable future by outlining key challenges, targeted recommendations, and the role of relevant stakeholders at the global, public, and individual level. The approach targets all age groups and socio-economic contexts and is innovative in its integration of systems-based thinking, digital health technologies, and health-promoting environments, all aligned with international frameworks such as the Global Action Plan on Physical Activity (WHO GAPPA), the UN Sustainable Development Goals (SDGs), and the Health in All Policies (HiAP) approach.Project or Policy Description: Although not yet implemented, this Joint Statement has been developed collaboratively by academic institutions, public health organisations, and civil society stakeholders across several European countries. It offers a strategic vision built on four guiding principles: prevention, inclusion, personalisation, and digital innovation.Development: This roadmap was co-created based on multidisciplinary, international collaboration and guided through existing research and policy frameworks.Implementation (Proposed): This proposal outlines future steps to integrate PA into global health policies, foster active public spaces (e.g. schools, workplaces), and deploy accessible, personalised digital tools to support individuals in adopting physically active lifestyles.Evaluation (Future): Recommendations have been formulated for measuring effectiveness through indicators such as stakeholder engagement, policy changes, health outcomes, and equity improvements.Dissemination (Future): Broader dissemination is envisioned through EU-wide networks, public campaigns, and open-access resources, with the goal of supporting large-scale adoption and adaptation.Conclusions: This Joint Statement serves as a blueprint for action, not yet implemented, but grounded in evidence and collective ambition. It outlines how coordinated efforts across policy, community, and individuals have the potential to transform the way physical activity is promoted and embedded in daily life. By providing a comprehensive roadmap – linking challenges, strategies, and stakeholders – it aims to catalyse systemic change, ensuring physical activity becomes a central pillar of healthier and more equitable societies in the years to come.Support/Funding Source: None.Keywords: Physical inactivity, health promotion, policy roadmap